Identification of Zingiberaceae as Useful Plant by Bidayuh Bau in Mount Sejinjang Singai and Mount Jagoi Bau, Sarawak - Ripen, Jovita Elderson; Meekiong, Kalu; Noweg, Gabriel Tonga (Science Research Publication., 2022)
The Zingiberaceae is a ginger family, consists of perennial herbs with creeping horizontal or tuberous rhizomes. It is comprised of about 53 genera and more than 1500 species that are distributed throughout Asia and more than 1200 species mostly growing in tropical forests. Borneo itself have more than 250 species of gingers in 19 genera. Sarawak has 141 species in 18 genera. Zingiberaceae is well known as gingers family with abundant numbers of spices widely used in Borneo, because of their unique flavors, ornamental and the medicinal values. The extracts of Zingiberaceae rhizome contain many essentials oils, including terpenes, alcohols, ketones, flavonoids, and phytoestrogens that use as medicine. Zingiberaceae grow vigorously in a wide range of habitats ranging from riverine to the mineral area, from lowland to the upper mountain regions. The utilization of Zingiberaceae as food, traditional medicine, spice, condiment, dye and flavour had been practiced by Bidayuh Singai and Jagoi in generation. Mount Sejinjang Singai was an old village own by Bidayuh Singai and Mount Jagoi was an old village own by Bidayuh Jagoi. Both villages have moved to new villages surrounding of each mountain area. They still practice the medicinal use of Zingiberaceae and some species are cultivated such as Zingiber officinale, Zingiber officinale var rubrum, Curcuma xanthorhiza, Curcuma domestica, Kaempferia galanga and Zingiber cassumunar. They mainly use for medicinal purposes as it can cure many diseases traditionally. These species are also sold in Bau local market by the local Bidayuh entrepreneur and digital online selling platform, Timogah.com.